Evaluation of Zinc Oxide-Eugenol, Zinc Oxide-Propolis and Endoflas as an Obturating Materials in Primary Molar Pulpectomies - A Comparative Study - Sunita Singh; Ashish Saxena; Vishal Khandelwal; Neha Verma; Arvind Jain (Indian Journal of Dental Research)
Background: The goal of effective primary tooth infection treatment is to keep the child healthy. The need to find the optimum root canal paste, however, was driven by the complex morphology of primary root canals and the desire for shorter therapy sessions. Aims: To evaluate and compare the clinical and radiographic success of zinc oxide eugenol, Zinc oxide-Propolis, and endoflas as obturating materials in the pulpectomy of primary teeth at 3, 6 and 9 months of follow-up. Materials and Methods: Pulpectomy of 60 nonvital primary molars was accomplished in 50 children aged 4–9 years. Teeth were randomly divided into three equal groups of 20 molars according to the type of root canal filling material. Pulpectomy was performed in a single or multiple visits depending on the condition of the tooth, and a stainless-steel crown was used for final restoration. Clinical and radiographic results were evaluated double-blindly at baseline (1 week), and at 3, 6 and 9 months, while radiographic results were evaluated at baseline (1 week), and at 6 and 9 months. Data were analysed using the Chi-square/Fisher’s exact test, and the P value was set at 0.05. Results: Endoflas and a mixture of zinc oxide powder with Propolis showed promising results (100%), whereas zinc oxide eugenol showed a lower success rate than the other two materials (85%). Conclusions: Endoflas and a combination of zinc oxide powder with Propolis can be a promising material as an alternative to Zinc Oxide Eugenol for obturation in primary teeth.